(3eYfi GdYTb heGgjJgs - (3CMeO Hf GdWjHs
(3ChdgG (B:s
(3bGd bdJ Ef GdYTb EaQGW aj GdeMHI hGdeMHI YdI GLJeGY GdGTjGA s
(3BNQgG (B:s
(3hLeGY Gdbhd ai gPG Cf GdUOGbI GJMGO faS GdeJUGObjf HGJaGb GdEQGOGJ hGddg GYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYTQhfs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(20 / 1035) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs